Object tracking in clutter and partial occlusion through rule-driven utilization of Snakes - Tsechpenakis, Gabriel; Rapantzikos, Konstantinos; Tsapatsoulis, Nicolas; Kollias, Stefanos D. (My University, 2003)
Efficient moving object tracking in cases of partial occlusion is a challenging task for the researchers in the fields of computer vision and video processing. In modern coding standards, like MPEG-4 and MPEG-7, the term of video objects is used to define moving objects in a video sequence. Automatic extraction of such objects is by no means trivial, and occlusion is one of the most important problems. This paper reformulates one of the most popular deformable templates for shape modeling and object tracking, the Snakes, in a probabilistic manner, in order to include providence for partial occlusion of the moving objects. Experiments of object tracking in partial occlusion, in complex natural sequences, where temporal clutter, abrupt motion and external lightning changes have been carried out, showing the efficiency of the proposed approach.
Keywords: Clutter; Computer graphics; Computer vision; Motion estimation